The Paradigm Root in Hebrew - Rubin, Aaron D. (Journal of Semitic studies, 2008)
In grammars of Hebrew, a variety of different roots have been used in order to illustrate the verbal paradigms. The reasons for choosing one root over another are worthy of examination, and ultimately such an exercise leads to the question of which root is ideal for this purpose. In fact, no one root is ideal, and the choice of paradigm root is ultimately connected with the goals of the individual authors.